Persistent Müllerian Duct Syndrome: Understanding the Challenges - Irene Chua; Naeem Samnakay (Case Reports in Urology)
Persistent Müllerian duct syndrome (PMDS) is a rare autosomal recessive condition defined by the presence of Müllerian duct-derived structures in an otherwise normally masculinized phenotypical and genotypical (46,XY) male. We describe the case of an infant diagnosed with PMDS, managed and followed up for 7 years. The diagnosis of PMDS was made at laparoscopy at 6 months of age for investigation and management of bilateral impalpable testes. A Müllerian structure resembling a uterus with bilateral fallopian tube-like structures was seen in the pelvis, along with bilateral intra-abdominal testes. Gonadal biopsy confirmed normal testicular tissue. The child underwent successful bilateral two-stage Fowler-Stephens orchidopexies. The Müllerian remnant was preserved to maintain testicular vascularity. At the most recent follow-up, the testes are intrascrotal and normal on palpation. There have been no clinical symptoms or concerns with the Müllerian remnant during surveillance with ultrasound and MRI. To date, there are less than 300 cases described in the medical literature, with limited consensus on management. We reflect on challenges the condition poses, including fertility preservation in PMDS, testicular and Müllerian malignancy risk in PMDS, and optimal management and surveillance of PMDS.